Case report: A rare case of very well-differentiated gastric adenocarcinoma of gastric type with a lymphovascular invasion - Chen, Jiaqi; Cui, Xiujie; Wu, Honglei; Zhou, Chengjun (Frontiers in Oncology, 2024)
Background: Very well differentiated gastric adenocarcinoma (VWDA) is a rare variant of gastric cancer, for which the diagnostic criteria and clinical behavior are not fully established. We reported a case of an intramucosal VWDA of gastric type with a lymphovascular invasion (LVI).Case presentation: A 67-year-old female visited our hospital for further treatment after a biopsy at the local hospital diagnosed as intramucosal gastric adenocarcinoma for three weeks. Endoscopic examination in our hospital showed a rough, slightly faded, 30mm flat-elevated lesion on the lesser curvature of the middle gastric body. Histopathologically, the lesion consisted of superficial foveolartype papillary adenocarcinoma and deep pyloric gland-type tubular adenocarcinoma. Immunostaining results showed that foveolar-type papillary adenocarcinoma was positive for MUC5AC and had a high index of Ki-67, but pyloric gland-type tubular adenocarcinoma was positive for MUC6 and had a low index of Ki-67. Both components were negative for MSH2 and MSH6 which suggested the microsatellite unstable high-phenotype (MSI-H). Moreover, a LVI was detected in the lesion. The pathological diagnosis was VWDA of gastric type.The case has unique histological and immunophenotypic characteristics, which not only indicates the importance of architectural features in the diagnosis of VWDA, but also further proves that the aggressive behavior of VWDA is correlated with tumor histological type and immunophenotype.